Quality Of Bakpao With The Use Of Different Steaming Equipment - Maharani, Annisa; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to analyze the effect of using different steaming base ingredients on the quality of the buns. This research is an experiment using 3 basic steaming materials (aluminium, stainless steel, bamboo) with 3 repetitions. The data analysis technique used is Analysis of Variance (ANAVA) to analyze sensory test data. The results of the sensory tests obtained quality including shape (neat) average values of X₁ (3.22), X₂ (3.22), X₃ (3.89). Shape (1/2 circle) average values of X₁ (3.39), X₂ (3.11), X₃ (3.11). Volume (expand) average values X₁ (3.22), X₂ (3.33), X₃ (3.22). Aroma (yeast-scented) mean values X₁ (3.22), X₂ (3.22), X₃ (3.89). Texture (slippery) average values X₁ (3.22), X₂ (3.11), X₃ (3.56). Texture (soft) average values X₁ (3.67), X₂ (3.89), X₃ (3.78). Texture (fine porous) average values X₁ (3.44), X₂ (3.33), X₃ (3.33). Taste (moderately sweet) average values X₁ (3.11), X₂ (3.11), X₃ (3.11). Based on the results of the sensory test, it was found that Fcount was greater than Ftable for the quality of the aroma of the buns, so it was continued with the Duncan test. X₁ and X₂ are not significantly different, X₁ and X₃ are significantly different. It was concluded that the results of the quality test of the buns using different steaming base materials were in the treatment (X₃) using bamboo-based steamers.